Maintenance Management at Sultan Abdul Samad Jamek Mosque, Kuala Lumpur: A Case Study - Rafikullah Deraman; Nur Asiela Mohd Ibrahim (Journal of Structural Monitoring and Built Environment, 2024)
Masjid Jamek Sultan Abdul Samad Kuala Lumpur (MJSASKL) is a historic landmark in Kuala Lumpur, established in 1909 and designated a National Heritage site by the National Heritage Department, Ministry of Unity, Culture, and Arts. As a center for worship, community activities, and tourism, maintaining its facilities' performance is crucial. Current maintenance practices primarily rely on corrective approaches, potentially hindering facility performance and leading to suboptimal management practices within the organization. This study aims to investigate the maintenance practices implemented by MJSASKL management. Using qualitative methods, structured interviews were conducted with key personnels from MJSASKL management and the Development Unit of JAWI. Findings reveal that while MJSASKL management has established a structured maintenance framework, challenges include limited maintenance personnel for assessing maintenance needs and adherence to maintenance budget guidelines set by the Department of Islamic Development Malaysia (JAKIM). The study contributes by providing insights that can support MJSASKL management and other stakeholders in effective facility maintenance management.